2017
DOI: 10.1186/s12884-017-1263-2
|View full text |Cite
|
Sign up to set email alerts
|

Option B+ for prevention of vertical HIV transmission has no influence on adverse birth outcomes in a cross-sectional cohort in Western Uganda

Abstract: BackgroundWhile most Sub-Saharan African countries are now implementing the WHO-recommended Option B+ protocol for prevention of vertical HIV transmission, there is a lack of knowledge regarding the influence of Option B+ exposure on adverse birth outcomes (ABOs). Against this background, we assessed ABOs among delivering women in Western Uganda.MethodsA cross-sectional, observational study was performed within a cohort of 412 mother-newborn-pairs in Virika Hospital, Fort Portal in 2013. The occurrence of stil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…However, a Ugandan study in the era of Option B+ and a systematic review by Uthman et al . found no association between stillbirth and preconception ART or timing of ART initiation respectively .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, a Ugandan study in the era of Option B+ and a systematic review by Uthman et al . found no association between stillbirth and preconception ART or timing of ART initiation respectively .…”
Section: Introductionmentioning
confidence: 83%
“…A cross‐sectional study in Western Uganda found that stillbirth was not more common among women who were on N(t)RTI/NNRTI‐based antiretroviral combinations than in HIV‐uninfected women, regardless of timing of initiation and adherence to antiretrovirals. The authors suggested that the positive effect of antiretrovirals on maternal HIV infection counterbalances their potential toxicity . A study conducted in Botswana found no differences in stillbirths between pregnant women taking either tenofovir/emtricitabine/efavirenz, other triple ART regimens, or zidovudine only .…”
Section: Discussionmentioning
confidence: 99%
“…On history of still birth, [79] [50,56], and shorter pregnancy interval, Mahande et al 2016 [39] showed effects. Besides, on UTI, Mahapula et al2016 [38], malaria, Rempis et al2017 [81], and obstetric complication Mekonen et al 2018 [52] had shown impact. The abovementioned studies were become out of pooled analysis.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Some studies found that adverse birth outcomes, such as increased preterm deliveries, stillbirths and low birth weight, occurred more frequently among HEI [3][4][5][6][7][8]. Other studies found no association between use of ART and adverse birth outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%